2022
DOI: 10.1016/j.breast.2022.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Optimal localization strategies for non-palpable breast cancers –A network meta-analysis of randomized controlled trials

Abstract: Mammographic screening programmes have increased detection rates of non-palpable breast cancers. In these cases, wire-guided localization (WGL) is the most common approach used to guide breast conserving surgery (BCS). Several RCTs have compared WGL to a range of novel localization techniques. We aimed to perform a network meta-analysis (NMA) of randomized controlled trials (RCTs) comparing methods of nonpalpable breast cancer localization. Methods: A NMA was performed according to PRISMA-NMA guidelines. Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 72 publications
(144 reference statements)
1
43
0
Order By: Relevance
“…Increasing use of breast conservation surgery, especially after downstaging following neoadjuvant chemotherapy (NACT), has led to an increase in the use of novel techniques such as Magseed ® , Radiofrequency Iodine seed (RFID) localization, Savi Scout ® , and Pintuition ® to assist in precisely excising tissue of interest in theatre; this coupled with the use of 3D intraoperative X-rays have greatly helped to reduce breast margin re-excision rates and improved cosmetic outcomes, leading to better patient satisfaction and reduced readmission rates. A significant advantage is the ease of inserting these localizers under local anaesthesia in outpatient settings under ultrasound guidance, and this can be kept in the breast for six months, which can help in surgical scheduling and resource optimization [ 10 , 11 , 12 , 13 ].…”
Section: Results and Discussion—innovations In Breast Cancer Carementioning
confidence: 99%
“…Increasing use of breast conservation surgery, especially after downstaging following neoadjuvant chemotherapy (NACT), has led to an increase in the use of novel techniques such as Magseed ® , Radiofrequency Iodine seed (RFID) localization, Savi Scout ® , and Pintuition ® to assist in precisely excising tissue of interest in theatre; this coupled with the use of 3D intraoperative X-rays have greatly helped to reduce breast margin re-excision rates and improved cosmetic outcomes, leading to better patient satisfaction and reduced readmission rates. A significant advantage is the ease of inserting these localizers under local anaesthesia in outpatient settings under ultrasound guidance, and this can be kept in the breast for six months, which can help in surgical scheduling and resource optimization [ 10 , 11 , 12 , 13 ].…”
Section: Results and Discussion—innovations In Breast Cancer Carementioning
confidence: 99%
“…Margin positivity and re-excision rates have been reported for completeness, although this study did not have enough power to detect a difference for these variables. For WL, Davey et al reported a positive margin rate of 20.1% and a surgical re-excision rate of 17.3% in a meta-analysis involving 24 randomized controlled trials [21]. In a review by Tayeh et al, the surgical re-excision rate for RFID localization was 13.9% [22].…”
Section: Discussionmentioning
confidence: 99%
“…Several large meta-analyses regarding the best localization technique for nonpalpable breast lesions included only a few of the techniques each time, 19,20 but so far, there is no conclusive superior localization technique that has been proven. A new prospective multicenter cohort study called the MELODY study (methods for localization of different types of breast lesions; NCT05559411) has therefore been initiated and is hopefully going to provide a better overview in the advantages and disadvantages of all available localization techniques for breast cancer, including 99m Tc ROLL 21 .…”
Section: Discussionmentioning
confidence: 99%